Longitudinal Assessment of Dental Erosion in a Romanian Cohort of Young Adults: A Ten-Year Follow-Up Pilot Study - Andrea Bors; Felicia Gabriela Beresescu; Melinda Szekely (Dentistry Journal)
Background: Dental erosion is the irreversible loss of tooth structure from acid exposure. Its prevalence is rising globally, making it an important oral health concern. However, longitudinal data from Eastern Europe are scarce, especially in Romania. This pilot study aimed to assess the 10-year incidence of dental erosion in Romanian young adults and to compare clinical index scoring with digital scanning. Methods: A 10-year prospective study followed 540 Romanian adults (aged 18–30) selected with no erosive lesions at baseline (Basic Erosive Wear Examination BEWE = 0). Erosive wear was assessed at the 10-year follow-up using BEWE, with 40 participants also undergoing digital intraoral scanning to measure enamel loss (μm). Gender differences were analyzed. Chi-square tests, relative risk, and correlation analyses were performed. Results: After 10 years, 23.2% of participants developed dental erosion. Males exhibited a higher incidence than females (29.9% vs. 17.2%; RR = 1.74, p < 0.001). Among the scanned subset (n = 40), the mean enamel loss was 137 ± 79 µm, with greater wear on palatal vs. buccal surfaces (p = 0.002). BEWE scores were moderately correlated with digital enamel loss (r = 0.58, p < 0.001). Conclusions: Erosion progressed over time in this cohort, with males at higher risk. Digital scanning detected subtle enamel loss not captured by BEWE, indicating greater sensitivity to early changes. BEWE and digital methods provided complementary information; their combined use offers a more comprehensive assessment.